A case of AndraStent® fracture in a patient with aortic coarctation: a review of the literature. (9th June 2020) - Cabrelle, Giulio; Milanesi, Ornella; Castaldi, Biagio
Abstract: Percutaneous treatment of aortic coarctation is based on angioplasty and/or stenting of the isthmus. We report a case of a 28-year-old girl suffering from aortic coarctation syndrome (coarctation + ventricular septal defect + bicuspid aorta). She underwent coarctectomy with subclavian flap and pulmonary bandage followed by ventricular septal defect closure and bandage removal in her first year of life. When she was 27 years old, a follow-up echocardiography detected an isthmic pressure gradient and a demodulated Doppler in abdominal aorta. A cardiac catheterisation confirmed the diagnosis of aortic re-coarctation. An AndraStent ® XL 48 mm was implanted with a resolution of the isthmic gradient. One year later, because of the reappearance of demodulated Doppler in abdominal aorta, a chest X-ray was performed, which showed a stent third-grade fracture. The fracture was corrected by positioning a covered stent cheatham platinum 45 mm through the fragments. The rarest complication after stenting procedures is the fracture of the device with an incidence between 0.01% and 0.08%. Pressure overload beyond the elastic threshold of the material and the pulsatile tension exerted by the blood flow on the walls of the stent are the main mechanisms at the base of the fracture, together with the compliance of the tissue. A vessel that underwent multiple surgical rearrangements could interfere with and complicate the physiopathology at the basis of the fracture. In conclusion, stenting is a safe technique to treat aortic coarctation; stent fracture is a rare event, and different anatomical and haemodynamic factors are related to this complication.